Dysregulation of miR-637 serves as a diagnostic biomarker in patients with carotid artery stenosis and predicts the occurrence of the cerebral ischemic event. Issue 1 (1st January 2021) - Zhang, Ting; Liu, Ruijie
ABSTRACT: The present research aims to explore the relationship between circulating microRNA and carotid artery stenosis (CAS). To evaluate the diagnostic significance of miR-637 in CAS patients and its potential predictive value for cerebral ischemia events through clinical studies. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to verify the differences in serum miR-637 between enrolled 97 CAS patients and 90 healthy individuals. Logistic regression analysis of the correlation between the level of miR-637 and the degree of carotid artery stenosis. The receiver operating characteristic (ROC) curve evaluated the diagnostic significance of miR-637 in identifying CAS patients from healthy individuals. Kaplan-Meier survival and Cox regression were used to evaluate the potential predictive ability of serum miR-637 levels during follow-up for cerebral ischemia events. Serum miR-637 of CAS patients was significantly reduced which was a good indicator of severe carotid stenosis ( P < 0.001). Reduced miR-637 can identify CAS patients from healthy individuals, demonstrating strong diagnostic capabilities. Furthermore, Kaplan-Meier analysis confirmed that the lower miR-637 levels in CAS, the more cerebral ischemia events (log-rank, P = 0.035), and the Multivariate Cox regressions confirmed that miR-637 was an independent predictor of CAS patients (HR = 0.073, 95%CI = 0.017–0.313, P < 0.001). We confirmed that serum miR-637 in CAS patients was significantly reduced. And reduced miR-637 was not only a potentially reliable biomarker for the diagnosis of CAS but also a useful indicator for predicting future cerebral ischemic events.